Perlindungan Lahan Pertanian Pangan Berkelanjutan Guna Memperkokoh Ketahanan Pangan Wilayah (Studi di Kabupaten Bantul, Daerah Istimewa Yogyakarta) - Gesti Ika Janti; Edhi Martono; Subejo Subejo (Jurnal Ketahanan Nasional, 2016)
ABSTRACTThe need for non-agricultural land tended to increased. This encouraged the conversion of agricultural lands and if it was not regulated, it may threatened food resilience. The Government had established Law Number 41 Year 2009 regarding Sustainable Food Agricultural Land Protection to controled agricultural land conversion. This study aimed to identified and analyzed Sustainable Food Agricultural Land Protection policy planning, the obstacles faced and the solving strategy to realized regional food resilience in Bantul Regency.The research method was descriptive analytical qualitative approach. Bantul regency was selected as the research location because it had high land conversions and had not implemented any regulation to followed up Law Number 41 Year 2009. Informants in this study were selected by purposive sampling technique from those who formulated the planning and implementation of Sustainable Food Agricultural Land Protection policy in Bantul Regency and also the farmers. The research variables were focused on aspects of land conversion, sustainable food agricultural land policy, and regional food resilience. Data was collected by in-depth interview, observation, documentation, and literature study. The research result showed that Bantul Regency had not seriously prepared Sustainable Food Agricultural Land Protection policy regulation. So far, several studies had been conducted as basis of regulation formulation. The main obstacles were previous spatial planning policy, disobedience to the spatial planning regulations, budget allocation, interest groups, farmer’s willingness and agricultural land availability. To strengthened regional food resilience, the Government of Bantul Regency reviewed spatial planning policy, enforced  law of spatial planning regulations, supported budget allocation, set the Sustainable Food Agricultural Land Protection regulation, increased land productivity, and  protected existing agricultural lands. Although generally, the condition of food resilience of Bantul Regency was in medium category, Sustainable Food Agricultural Land Protection regulation must be implemented immediatelyABSTRAKKebutuhan lahan non pertanian cenderung mengalami peningkatan. Hal ini mendorong terjadinya alih fungsi lahan pertanian dan apabila tidak dikendalikan dapat mengancam ketahanan pangan. Pemerintah telah menetapkan Undang-Undang Nomor 41 Tahun 2009 tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan untuk mengendalikan alih fungsi lahan pertanian. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis perencanaan kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan, kendala yang dihadapi serta strategi pemecahannya guna mewujudkan ketahanan pangan wilayah di Kabupaten Bantul.Metode penelitian menggunakan pendekatan kualitatif yang bersifat deskriptif analisis. Kabupaten Bantul dipilih menjadi lokasi penelitian karena mengalami aktivitas alih fungsi lahan yang tinggi dan belum menetapkan regulasi untuk menindaklanjuti Undang-Undang Nomor 41 Tahun 2009. Informan dalam penelitian ini diambil melalui teknik purposive sampling yang merupakan penyusun perencanaan sekaligus pelaksana kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kabupaten Bantul serta petani. Variabel penelitian difokuskan pada aspek alih fungsi lahan, kebijakan perlindungan lahan pertanian pangan berkelanjutan, dan ketahanan pangan wilayah. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dokumentasi, dan studi pustaka. Hasil penelitian menunjukkan Pemerintah Kabupaten Bantul belum serius dalam mempersiapkan regulasi kebijakan Perlindungan Lahan Pertanian Pangan Berkelanjutan. Sejauh ini telah dilakukan beberapa studi sebagai dasar penyusunan regulasi. Kendala utama terletak pada kebijakan penataan ruang yang telah disusun sebelumnya, pelanggaran hukum regulasi penataan ruang wilayah, alokasi anggaran perencanaan regulasi, interest groups, kesediaan petani dan ketersediaan lahan pertanian. Untuk memperkokoh ketahanan pangan wilayah, Pemerintah Kabupaten Bantul melakukan peninjauan kembali terhadap kebijakan penataan ruang, penegakkan hukum regulasi penataan ruang, pengalokasian anggaran, penetapan regulasi Perlindungan Lahan Pertanian Pangan Berkelanjutan, pemberian insentif, serta melakukan kegiatan optimasi lahan, sertipikat tanah petani dan sinkronisasi data lahan pertanian. Meski secara umum kondisi ketahanan pangan wilayah di Kabupaten Bantul dikategorikan sedang, regulasi Perlindungan Lahan Pertanian Pangan Berkelanjutan mendesak untuk segera ditetapkan.